DEVELOPMENT OF TEACHING MATERIAL WITH BRIDGING ANALOGY: LESSON PLAN & MODULE - Febiana Gita; Finola Marta Putri; Gelar Dwirahayu (ALGORITMA: Journal of Mathematics Education, 2022)
This study aims to develop teaching materials consisting of a lesson plan and module with the Bridging Analogy Approach for subject matter Relations and Functions. Bridging Analogy is an approach that connects new concepts with analogous real-life problems for the student to a new concept in math by looking for the similarity between the analogy and the new concept. The research method used is Research and Development (R&D), consisting of Define, Design, and Develop and for the disseminate can't be implemented because of pandemic covid-19. The expert and student judged the teaching material. The expert who asses the teaching material consists of 3 lectures from the Math Department and two Junior High School practitioners. The score for the teaching material with Bridging Analogy by the expert is 93.83%, which means the lesson plan is "worthy," and the score for the module is 91.26%, which means the module is "worthy." Thus the module was assessed by the student from SMPN 178 Jakarta to know the teaching material's effectiveness and clarity. The response score from students about the module is 93.62%, meaning the module is "worthy." The conclusion is teaching material: lesson plan and module in this study can be implemented for teaching and learning relations and functions at Junior High School.